Enhanced beings : human germline modification and the law / Kerry Lynn Macintosh. - Macintosh, Kerry Lynn (Cambridge University Press, 2018)
Today, scientists are using CRISPR/Cas9 and other molecular editing tools to alter human gametes and embryos, a practice known as human germline modification. In the near future, these efforts may lead to the birth of children with better health, improved memories, and extended lifespans. However, critics claim that human germline modification exceeds divine and natural boundaries, transforms reproduction into manufacture, and yields apocalyptic outcomes such as the collapse of democracy. Enhanced Beings: Human Germline Modification and the Law analyzes and critiques these objections on both biological and political grounds. Professor Kerry Lynn Macintosh discusses the hidden psychology behind the objections, and describes the laws that affect this new technology. Provocative and timely, Enhanced Beings argues that bans on human germline modification pose a threat to scientists and science, parents, children, foreigners, and society.